2021
DOI: 10.3390/cancers13164218
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Jugular Foramen Schwannomas

Abstract: Background: Resection of jugular foramen schwannomas (JFSs) with minimal cranial nerve (CN) injury remains difficult. Reoperations in this vital region are associated with severe CN deficits. Methods: We performed a retrospective analysis at a tertiary neurosurgical center of patients who underwent surgery for JFSs between June 2007 and May 2020. We included nine patients (median age 60 years, 77.8% female, 22.2% male). Preoperative symptoms included hearing loss (66.6%), headache (44.4%), hoarseness (33.3%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In most cases, only the distal part of the sigmoid sinus is exposed while the opening of JF is facilitated both by the bone erosion and the JF enlargement produced by the tumor growth. 1,3-7,12-20 This may be not necessary in type C of JFs and in all our cases. Thanks to this, it is not necessary to drill the temporal petrous bone, so the risk of VII cranial nerve damage is decreased.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In most cases, only the distal part of the sigmoid sinus is exposed while the opening of JF is facilitated both by the bone erosion and the JF enlargement produced by the tumor growth. 1,3-7,12-20 This may be not necessary in type C of JFs and in all our cases. Thanks to this, it is not necessary to drill the temporal petrous bone, so the risk of VII cranial nerve damage is decreased.…”
Section: Discussionmentioning
confidence: 78%
“…Because of their low incidence and the clearly difficult anatomical features of the region, JFs correct management is still discussed in the literature. 1,3-7,12-20 We experienced and recommend ELJA. In this approach, the surgical position described increased space in the surgical field; it improves lateral posterior view; in addition, it limits VA rotation and atlas displacement.…”
Section: Discussionmentioning
confidence: 98%
“…Most operations were performed with the retrosigmoid approach (36.5%) combined with suboccipital craniotomy (23.2%), with the far-lateral approach (29.7%) combined with suboccipital craniotomy and cervical laminectomy (15%), or with the posterior approach combined with cervical laminectomy (26.9%). The extreme lateral infrajugular transcondylar–transtubercular exposure (ELITE) was performed in 16 patients (4.5%) [ 30 , 31 ], and the endoscopic transoral resection in 8 (2.3%) [ 32 , 33 , 34 ]. Jiang et al [ 11 ] also reported the use of occipitocervical fusion in 6 patients (1.7%) after cervical laminectomy and facetectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical pictures of CVJ schwannomas mirror their anatomy, with most patients experiencing headache and neck pain as primary symptoms [ 10 , 12 ]. The high frequency of sensory disturbances likely stems from the sensory nerve roots’ tumor origin, while other impairments are caused by tumors compressing contiguous structures, such as lower cranial nerves (hoarseness, speech disorders, hearing disturbance), cerebellum (ataxia), and brainstem/cervical spinal cord (motor disorders) [ 31 , 36 , 54 ]. Tongue atrophy is typical in hypoglossal schwannomas [ 40 ], while evident neck masses may be found in otherwise asymptomatic slow-growing C1–C2 tumors [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation